DEVELOPMENT OF PILGRIMAGE TOURISM IN UZBEKISTAN DURING THE YEARS OF INDEPENDENCE AND ITS METHODOLOGICAL FOUNDATIONS - Fariza Yelmuradovna Khalmuratova (Scientific Impulse, 2024)
The article talks about the focus on tourism in the years of independence, extensive tourism reform, raising our nationalism and promoting national tourism.